Kepuasan Nasabah Terhadap Pelayanan BRI Unit Bunta Kabupaten Banggai: Customer Satisfaction with BRI Unit Bunta Services Banggai District - Arpan Kurubit; Selvince; Heny Ariwijaya (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2022)
Service quality influences satisfaction, a feeling of satisfaction is felt if the expectations and performance match each other, but if the expectations are not by the performance, then what is supposed to be a feeling of disappointment. This study aimed to determine the effect of service quality partially and simultaneously on customer satisfaction to find out how much influence service quality had on customer satisfaction at Bank Rakyat Indonesia Bunta Unit Banggai Regency. The analytical method used is multiple linear regression analysis, determination, correlation, t-test, and F, with 100 samples using the Slovin technique. Based on the results of research and testing, it is concluded that the multiple linear regression equation Y = 0.741 + 0.247X1 + 0.278 X2 + 0.264X3 + 0.176X4 + 0.220X5. Service quality partially or simultaneously affects customer satisfaction at Bank Rakyat Indonesia Unit Bunta Banggai Regency. The relationship between service quality and customer satisfaction at Bank Rakyat Indonesia Unit Bunta Banggai Regency is in a strong category, and the contribution of service quality variables to customer satisfaction is 62.1%. The remaining 37.9% is influenced by other variables not included in this study.